The Modified Otago Exercises Prevent Grip Strength Deterioration Among Older Fallers in the Malaysian Falls Assessment and Intervention Trial (MyFAIT). - Liew, L.; Tan, M.; Tan, P.; Mat, S.; Majid, L.; Hill, Keith; Mazlan, M. (2018)
BACKGROUND AND PURPOSE: Exercise-based interventions, such as the Otago Exercise Program (OEP), are effective in preventing falls in the older adult. Previous studies evaluating the OEP have determined falls, lower limb strength, or balance outcomes but with lack of assessment of hand grip strength. The objective of this study is to evaluate the effect of OEP on hand grip strength alongside mobility and balance outcomes. METHODS: This was a single-center, prospective, and single-blind randomized controlled trial conducted at the University Malaya Medical Centre. Patients older than 65 years presenting to the hospital emergency department or geriatric clinic with 1 injurious fall or 2 falls in the past year and with impaired functional mobility were included in the study. The intervention group received a modified OEP intervention (n = 34) for 3 months, while the control group received conventional care (n = 33). All participants were assessed at baseline and 6 months. RESULTS: Twenty-four participants in both OEP and control groups completed the 6-month follow-up assessments. Within-group analyses revealed no difference in grip strength in the OEP group (P = 1.00, right hand; P = .55, left hand), with significant deterioration in grip strength in the control group (P = .01, right hand; P = .005, left hand). Change in grip strength over 6 months significantly favored the OEP group (P = .047, right hand; P = .004, left hand). Significant improvements were also observed in mobility and balance in the OEP group. CONCLUSIONS: In addition to benefits in mobility and balance, the OEP also prevents deterioration in upper limb strength. Additional benefits of exercise interventions for secondary prevention of falls in term of sarcopenia and frailty should also be evaluated in the future.